1945
DOI: 10.1084/jem.81.5.423
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis, Storage, and Excretion of Creatine, Creatinine, and Glycocyamine in Progressive Muscular Dystrophy and the Effects of Certain Hormones on These Processes

Abstract: The diminished excretion of creatinine in progressive muscular dystrophy is a more striking and specific phenomenon than the excess excretion of creatine, marked though this is. While creatinuria is invariably encountered in all cases of long-standing dystrophy, the extent to which the excretion of creatinine is decreased provides a more reliable indication of the severity of the disease since an excess output of creatine may occur physiologically in normal human subjects and in many pathological conditions no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1946
1946
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In man there is reason to believe that most or all creatine synthesis occurs in the liver (9) and it is, therefore, suggested that in progressive muscular dystrophy the creatinuria is a consequence of-an imbalance between normal hepatic creatine synthesis, and markedly diminished creatine uptake by-muscle. This view is in accord with that expressed by Hoagland, Gilder, and Shank (10).…”
Section: Resultssupporting
confidence: 90%
“…In man there is reason to believe that most or all creatine synthesis occurs in the liver (9) and it is, therefore, suggested that in progressive muscular dystrophy the creatinuria is a consequence of-an imbalance between normal hepatic creatine synthesis, and markedly diminished creatine uptake by-muscle. This view is in accord with that expressed by Hoagland, Gilder, and Shank (10).…”
Section: Resultssupporting
confidence: 90%
“…Creatinine is derived from the metabolism of creatine, which is transformed into phosphocreatine and used by muscles as an energetic substrate (Hoagland et al, 1945 ). A higher production of creatinine is linked to a higher use of phosphocreatine and, consequently, to greater muscular efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiologic states associated with muscle wasting and reduced muscle mass also feature reduced creatinine generation. Such conditions include chronic glucocorticoid therapy (9), hyperthyroidism (10), muscular dystrophy (11, 12), muscular paralysis (10, l3, 14), dermatomyositis and polymyositis (10), and all causes of negative nitrogen balance (5).…”
Section: Sources and Sites Of Creatinine Generationmentioning
confidence: 99%